Fatores de produção, agricultura e desenvolvimento econômico regional no Brasil - Alcantara, Isabela Romanha de (2020)
Brazilian agricultural production is globally important. Brazil is the main producer and exporter of various products and commodities. Brazilian history is mixed with the performance of agricultural activities in the country. Studying the production factors, such as land, labor, and technology, became relevant to verify the core of the competitiveness of Brazilian agriculture. However, we seek to question how each production factor is used in Brazilian agriculture. It is in this context that the general objective of this paper is to analyze the use of production factors in Brazilian agriculture, as well as their spatiality between 2006 and 2017. The theoretical foundation presents the main lines of classic and contemporary thoughts on economic and regional development. The literature review focuses on the main studies on the production function and the factors of land, labor, and technology. The Exploratory Spatial Data Analysis (ESDA) and Spatial Econometric were the methodological procedures used, besides a literature review on the theme. Innovation and technology have helped Brazil in the process of regional economic development, which Brazilian agriculture is an example to illustrate this process. The spatial organization of agricultural production and its factors have remarkable characteristics in the Brazilian context, which association pattern was positive (indicating the presence of agglomerations) for all production factors, especially knowledge-related technology. In addition, this non-physical technology was also the most important factor in both 2006 and 2017, according to econometric results. Physical technology, related to the use of agricultural tractors, was the second most important element to determine the value of agricultural production. Nevertheless, the importance of the labor factor slightly changed over time while the land factor was not significant for the value of agricultural production. It was also noticed that spatiality influences the value of agricultural production, given the spillover effect.